PROSEDUR PEMILIHAN DAN KEWENANGAN PEJABAT KEPALA DAERAH PADA KEKOSONGAN JABATAN KEPALA DAERAH MENJELANG PEMILIHAN KEPALA DAERAH SECARA SERENTAK PADA 2024 - Sangaji, Muhamad kautsar (SUPREMASI HUKUM, 2024)
The procedure of Election Acting Regional Head and Authority Regional Head during Election in 2024 be regulated by Regulation of Domestic Minister Republic Indonesia 4 of 2023. The procedure of Election Acting Regional Head consists proposal of the candidate Acting Regional Head, Discussion of candidate Acting Regional Head, Decide of Acting Regional Head, and Appointment of Acting Regional Head. Acting Regional Head have same duties, authorities, obligations, and prohibitions Governors, Regents and Mayors in accordance with the provisions of laws and regulations regarding regional government. This research method is normative juridical. Normative juridical, namely the author analyzes the problem by using articles in a statutory regulation and various literatures such as books, journals, theses, dissertations and dictionaries as references in writing this research. Keywords: Acting Regional Head, Election Acting Regional Head, Authority Regional Head Â